Dos especies nuevas de Pleurothallidinae (Orchidaceae) de México - Solano Gómez, Rodolfo (Lankesteriana: International Journal on Orchidology, 2013)
Two new species of subtribe Pleurothallidinae are described and illustrated as Acianthera sotoana, from Oaxaca and Veracruz, and Stelis sotoarenasii, from Oaxaca. These orchids have been previously confused with similar species, the former with Acianthera johnsonii, the latter with Stelis retusa. For each species information about distribution, habitat, phenology, conservation status, and a map with their known localities are provided.